Environmental Strategies in Enterprises of The Energy Sector and the Role of The Ecological Audit in Them - Agnieszka MAZUREK-CZARNECKA; Piotr Paweł MAŁECKI; Renata ŻABA-NIERODA (Communications of International Proceedings, 2022)
The work attempts to identify issues of particular importance in the field of eco-audit, implemented in enterprises from the power sector. The requirements of the Eco-Management and Audit Scheme EMAS constitute guidelines, thanks to which it is possible to organize the obligations in the field of environmental protection, optimize the costs incurred, and efficiently manage energy and resources. The Eco-Management and Audit Scheme EMAS is also a reliable environmental reporting system for an organization that facilitates open dialogue with stakeholders. Relations between the enterprise and its environment are particularly important at present and have a huge impact on the functioning of enterprises in relations with their stakeholders. Confirmed audit activities in the field of environmental protection are particularly important in this context. It is a useful tool for creating a culture of sustainable development in organizations and for the effective management of available resources and energy. The requirements of the eco-management and audit scheme EMAS provide guidelines, specific guidelines, thanks to which organizations organize their obligations in the field of environmental protection, optimize the costs incurred and efficiently manage energy and resources. The eco-management and audit system EMAS is also a reliable system for reporting the environmental impact of an organization, which facilitates an open dialogue with interested parties. Registration in the eco-management and audit scheme EMAS means that the organization meets the most stringent environmental protection requirements. It is the prestige of being in the group of companies that conduct their activities in accordance with the idea of ​​sustainable development. Prestige confirmed by a certificate granted by the General Director for Environmental Protection.
Keywords: Environmental strategies; energy sector; ecological audit; EMAS